Locutionary and Illocutionary Acts by Anies Baswedan in the First Presidential Candidate Debate in 2024 - Vina Handayani; Hanafi Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2025)
Understanding meaning in political discourse is crucial, as a speaker’s intentions shape public perception and influence audience perspectives. While many studies have explored speech acts in political contexts, there is still limited analysis focusing specifically on the locutionary and illocutionary acts of Indonesian presidential candidates, particularly in the 2024 debates. This study aims to analyze the types and frequency of locutionary and illocutionary acts used by Anies Baswedan in the first presidential candidate debate of 2024, as well as to interpret the meanings embedded in these speech acts. Employing a qualitative descriptive design, the research collects data in the form of clauses containing types of locutionary and illocutionary acts as the primary source, which then were identified and categorized. The findings reveal 40 instances of locutionary acts, dominated by assertive acts (26), followed by phonetic acts (14) and retic acts (8). Additionally, 42 illocutionary acts were identified, with phatic actions (18) being the most frequent, followed by phonetic (14) and retic actions (8). The analysis uncovered that many of these acts carried persuasive meanings aimed at convincing listeners during the debate. This study offers insights into how Indonesian political figures strategically use language, providing a basis for future research on persuasive speech in political campaigns.